2014
DOI: 10.1177/0008417414552187
|View full text |Cite
|
Sign up to set email alerts
|

An international systematic mapping review of fieldwork education in occupational therapy

Abstract: Three recommendations were identified: strengthen procedures for studying singular fieldwork experiences, broaden rationales for studying fieldwork, and translate educational concepts for occupational therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
26
0
3
Order By: Relevance
“…Their results can highlight gaps in the literature, inform future research priority areas and provide health professional educators with direction on their research and education activities . Such reviews have been beneficial in providing guidance for academic and educational activities in other health professions including occupational therapy and medicine . Despite the existence of an increasingly vast body of health professions’ education literature, profession‐specific education research can be used to better prepare students to address future challenges…”
Section: Introductionmentioning
confidence: 99%
“…Their results can highlight gaps in the literature, inform future research priority areas and provide health professional educators with direction on their research and education activities . Such reviews have been beneficial in providing guidance for academic and educational activities in other health professions including occupational therapy and medicine . Despite the existence of an increasingly vast body of health professions’ education literature, profession‐specific education research can be used to better prepare students to address future challenges…”
Section: Introductionmentioning
confidence: 99%
“…Students’ final scores across the eight SPEF–R domains were in the higher range, supporting previous research that highlights practice education as an opportunity for students to develop their toolbox of communication, thinking and procedural skills and coping capacities as well as an opportunity to consolidate theory knowledge and skills learnt in the classroom context. (Roberts et al, ). These findings also signify the importance of practice education placements providing practical experiences in authentic contexts that encourage the development of students’ professional self‐identity (Roberts et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(Roberts et al, ). These findings also signify the importance of practice education placements providing practical experiences in authentic contexts that encourage the development of students’ professional self‐identity (Roberts et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In occupational therapy, systematic mapping studies have found that academic and fieldwork education research is characterized by descriptive inquiry methods used to study learning activities in local contexts, where student perceptions are the primary outcomes; however, studies frequently omit theoretical frameworks and use of philosophy, history, and theory as windows on data (Hooper, King, Wood, Bilics, & Gupta, 2013;Roberts, Hooper, Wood, & King, 2014). While much of the work in occupational therapy education research can be classified as descriptive, it is not as if it has been intentionally and systematically descriptive.…”
Section: The Lack Of Philosophical Historical and Theoretical Inquimentioning
confidence: 99%